Recent Progress in Turning Waste into Catalysts for Green Syntheses - Konstantin Wink; Ingo Hartmann (Sustainable Chemistry, 2024)
The recycling of catalysts has emerged as a key solution to address environmental pollution and the scarcity of natural resources. This dynamic is further reinforced by the growing industrial demand for catalysts and the urgent need to transition to more sustainable production methods. In the context of chemical transformations, the direct reuse of recycled catalysts for chemical applications in particular represents an elegant route towards greener syntheses. In this article, we review recent advancements in the recycling of homogeneous and heterogeneous catalysts since 2020, emphasizing the utilization of waste-derived catalysts for chemical reactions. In particular, we consider three primary sources of waste: electronic waste, spent lithium-ion batteries, and industrial wastewater. For each of these waste streams, different extraction methods are explored for their effectiveness in obtaining catalysts suitable for a broad spectrum of chemical reactions. These presented studies emphasize the potential of recycled catalysts to contribute to a sustainable and waste-efficient future.